Exploring Racial Discrimination Against Black Teens in ’Light It Up’ by Kekla Magoon - Vira Adelia (Morphosis: Journal of Literature, 2024)
This study aims to analyzed the racial discrimination issue that portrayed in the Light It Up novel by Kekla Magoon. The writer analyzed the racial discrimination in the novel by using the theory of Delgado & Stefancic. Besides, this study uses a qualitative approach, which is revealing the main issue by describing it in the form of sentences and paragraphs. The data collection was obtained by classifying some points that related to racial discrimination and the responses of black teenagers. The result of this study shows that there are three aspects of racial discrimination, they are normal racism, interest convergent (material determinism), and social construction. From all the data that have been analyzed, social construction is the dominant data in this study. Moreover, this study shows the white brutality and prejudice behavior toward African American teenagers. In conclusion, this study portrays that racial discrimination has negative impacts on the lives of black teenagers. Keywords: Black Teenager, Prejudice, Racial Discrimination, Response to Racial Discrimination